Conducting films based on single-component molecular metals1. Issue 66 (25th August 2015) - Alves, H.; Neves, A. I. S.; Gouveia, W.; Silva, R. A. L.; Belo, D.
<x xml:space="preserve">Abstract</x> We demonstrate that single component molecular metals can be used as conductive inks for printed electronics.